A STUDY OF CHINESE INBOUND TOURISM DEMAND IN SRI LANKA: AN ANALYSIS OF TOURIST BEHAVIOURAL CHARACTERISTICS - Basnayaka, S.; Silva, D.A.C. Suranga (Department of Economics, Faculty of Arts, University of Colombo, 2017)
Sri Lanka is one of the major developing tourist destinations where tourism has huge potential to grow thereby supporting the national economy of Sri Lanka. According to Sri Lankan Tourism Development Authority the tourists arrivals in Sri Lanka is more than 2 million in 2016, which has been drastically increased after end of civil war which was lasted for 26 years. After analyzing the importance and contribution of the tourism industry to the economy, Sri Lanka has begun an aggressive promotion of the destination on the theme of The Wonder of Asia.Sri Lanka has traditionally branded, promoted, and carried out marketing and promotional strategies aiming at Western & European markets. Now , however, considering the rapidly growing market and the vast potential of the East Asian region, specially Chinese outbound tourism, Sri Lanka has decided to shift its traditional market strategieswhich will aim at attracting a larger number of tourist arrivals from China than which is presently experienced.
Keywords: Chinese inbound Tourist , Tourism Demand ,Tourist Behaviour